Texts Archaeology: method, techniques and reflections for reading fragments of ancient literary works - Maranhão, Marcello de Albuquerque (Romanitas - Revista de Estudos Grecolatinos, 2013)
Review of: BARON, Christopher. Timaeus of Tauromenium and Hellenistic Historiography. Cambridge Univesity Press, Cambridge, Inglaterra, 2013. 317 p.
Keywords: Archeology of Texts; Reading Methods; Ancient texts